Abdominal actinomyces infection simulating malignant neoplasm: A case report - Fong, Wan Lee; Wui, JasmineThing Kueh; Dayangku Norlida, Awang Ojep; Xiu, Christine Ting Wong (2021)
Introduction: Actinomycosis is a rare chronic infection caused by filamentous anaerobic bacteria of the genus Actinomyces. Abdominal infection mostly involved the ileo-caecal area and can mimick malignant tumour in clinical and radiological examination. Case report: An 82-year-old woman presented with lower abdominal pain for 1 month with palpable abdominal mass. CT TAP showed an infiltrating, heterogenous left lateral abdominal wall mass which might represented primary muscle tumour or metastatic deposit, measuring 5.8x 5.3x2.5 cm. Biopsy was done and showed spindle cells proliferation with inflammation likely caused by infective origin. Laparoscopic converted open excision of left lateral abdominal wall revealed a mass infiltrating the transverse colon and omentum. We received a mass, covered with greenish suppurative exudate and attached to a segment of colon. Histology examination showed an inflammatory and fibrotic mass arising from the outside of the bowel wall with intact andunivolved colon mucosa. There were scattered actinomyces colonies and microabscess seen in the pericolonic tissue. Discussion: Actinomyces secrete proteolytic enzymes and therefore have the tendency to infiltrate the adjacent tissue. Multiorgan involvement is also possible. Culture is difficult because of the anarobic character and the slow growth of actinomyces. Despite CT scan, FNAC and culture, the diagnosis is usually ascertained after histologic examination. Conclusion: This case is presented for its rarity and diagnostic dilemma it presented, be it clinically or by the small biopsy. In conclusion, abdominal actinomycosis is to be considered in the differential diagnosis of an abdominal mass.